Potential Target Receptors for the Pharmacotherapy of Burning Mouth Syndrome - Takahiko Nagamine (Pharmaceuticals)
Objective:Burning mouth syndrome (BMS) is a chronic, intractable orofacial pain condition characterized by a burning sensation in the oral mucosa without discernible lesions. The syndrome predominantly affects menopausal and postmenopausal women and is considered a form of nociplastic pain, where the processing of pain stimuli is altered. Given the significant sex disparity, it is crucial to consider underlying neurobiological differences that may inform treatment. This review explores potential pharmacological targets by examining the pathological mechanisms of BMS. Method of Research: A narrative review approach was utilized to systematically explore and synthesize literature regarding the pathophysiology of BMS and to identify receptors implicated in the enhancement of sensory transmission and the altered processing of pain stimuli. Results: The mechanism of enhanced sensory transmission points to receptors such as TRPV1, P2X3, and CB2 as potential targets. However, considering the nociplastic nature of BMS and its prevalence in women, mechanisms involving altered central pain processing are paramount. Research indicates significant sex differences in glutamate transmission and plasticity within reward-related brain regions. This suggests that the N-methyl-D-aspartate (NMDA) receptor, a cornerstone of glutamate signaling and synaptic plasticity, is a primary therapeutic target. Furthermore, the altered processing of pain and reward, which is a key feature of chronic pain, implicates the brain’s dopaminergic system. A decrease in dopamine D2 receptor function within this system is believed to contribute to the pathology of BMS. Estrogen receptors are also considered relevant due to the menopausal onset. Conclusions: Based on the evidence, the most promising targets for pharmacotherapy in BMS are likely the NMDA receptor and the dopamine D2 receptor. The high prevalence of BMS in women, coupled with known sex differences in the glutamate and dopamine pathways of the reward system, provides a strong rationale for this focus. Effective treatment strategies should therefore aim to modulate these specific systems, directly or indirectly controlling NMDE receptor hyperactivity and addressing the decreased D2 receptor function. Further research into therapies that specifically target this sex-linked neurobiology is essential for developing effective pharmacotherapy for BMS.